Ultra-rapid and sensitive detection of African swine fever virus using multiple cross displacement amplification combined with nanoparticle-based lateral flow biosensor - Mao, Sha; Zhang, Renjun; Yang, Xinggui; Huang, Junfei; Kang, Yingqian; Wang, Yi; Chen, Hong; Li, Shijun (Frontiers in Microbiology, 2024)
African swine fever (ASF) is a devastating disease that can kill almost all infected pigs, causing great damage to the pig industry and destabilizing the global economy. Here, we developed a specific assay that combined multiple cross-displacement amplification (MCDA) with a nanoparticle-based lateral flow biosensor (LFB) for early and rapid identification of the African swine fever virus (ASFV-MCDA-LFB). We first designed a set of MCDA primers to recognize 10 different regions of the target ASFV B646L gene. Subsequently, the MCDA reaction was monitored with various methods: MG chromogenic reagents, agarose gel electrophoresis, real-time turbidity, and LFB. The ASFV-MCDA-LFB assay was optimized and evaluated with target nucleic acid templates extracted from various pathogens and simulated whole blood samples. As a result, the detection of limit (LOD) of the ASFV assay was 200 copies/reaction within 30 min, and no cross-reaction were observed with other non-ASFV viruses and common pathogens in this study. The evaluation assays demonstrated that the ASFV-MCDA-LFB method here is rapid, objective, easy-to-use, and low-cost detection method which can be used as a diagnostic or screening tool with competitive potential for point-of-care testing (POCT) of ASFV.